Analysing the usage of a segregated interurban cycleway (Greenway) in Ireland - CAULFIELD, BRIAN (My University, 2012)
This paper analyses the usage of a pilot greenway in a rural environment in Ireland. The path is 42 km long and has several settlements and schools located along the route. A survey was conducted in five schools along the route, to determine the usage of the greenway by students and staff in the schools. This enabled observations to be made in relation to the usage of the greenway. Usage of the path is established by means of counters located along the route. Average hourly day profiles of usage along the path were created for different scenarios. This allowed the differences in usage to be examined. The impact of national and public holidays was also observed. Usage patterns are also analysed in relation to a number of weather variables. The relationships are determined by means of regression analysis. The cost of construction of the path is known and therefore by establishing the user numbers the cost per trip can be calculated. The average spend of a tourist in Ireland is known, and the quantity of tourists needed to pay for the path is estimated. The analysis in this paper determined that there is a strong increase in the cycling and walking rate in the areas immediately surrounding the Greenway in persons accessing places of education. The paper also determined that usage is higher when there is a combination of the following variables; temperature is above 13.15 C and sunshine hours are between 9.4 and 2.3 hours
91st Annual Meeting of the Transportation Research Board
PUBLISHED
Washington D.C.
Keywords: Transport; Smart & Sustainable Planet